Epidemiology and molecular biology of elephant endotheliotropic herpesvirus 1 in the Asian elephant Elephas maximus - Bennett, Laura (2018)
Herpesviruses are ubiquitous and are found worldwide, most animal species can be infected with multiple herpesviruses. Some cause clinical disease and others remain symptomatic throughout life. Herpesviruses are found in both captive and wild animals including Asian elephants (Elephas maximus). Elephant Endothelioltropic Herpesvirus (EEHV) has been reported in both captive and wild Asian elephants, with a number of cases being reported in North America, Europe and Asia. It has been suggested that EEHV is associated with haemorrhagic disease, which has been attributed to a number of Asian elephant deaths, affecting mostly juveniles and calves. Clinical signs can vary from weight loss, lethargy, depression, cyanosis of the tongue and sudden death. Molecular testing using qPCR has enabled the detection of individual variants of EEHV, this thesis investigates the EEHV1 variant. EEHV1 has been highlighted as the variant that is more frequently associated with deaths. This thesis includes five studies investigating different aspects of EEHV. Including, the relationship between pregnancy and EEHV viral shedding, the use of an amended human protocol for culturing endothelial cells, EEHV tissue tropism, a potential genetic or familial link between EEHV associated deaths and the detection of potential co-pathogens. The main findings from this thesis include: 1) the use of a longitudinal study investigating a potential link between the physiological stress of pregnancy and EEHV viral shedding. This study suggested there was no link between pregnancy and EEHV viral shedding however other stressors may be involved. 2) Using an amended human umbilical vein endothelial cell protocol, the culture of Asian elephant endothelial cells was successful. The cells from this study may be used in subsequent drug testing and vaccine development. 3) Quantitative PCR was used to determine EEHV1 tropism in tissues from two deaths associated with the virus. Tropism appeared to be for the heart and liver. 4) This thesis provides results from a preliminary study into a potential link between EEHV associated deaths. The data from an Asian elephant genogram shows there is the possibility of a genetic or familial link, which requires further investigation. 5) A number of tissues from deaths associated with EEHV and or death from other causes were investigated for the presence of potential co-pathogens, including the presence of encephalomyocarditis virus (EMCV), using microarray technology. The results indicated there were no co-pathogens present in the tissues. This thesis adds to the current published data, and includes the first known preliminary study investigating a potential genetic link between elephant deaths due to EEHV.